Can Ebola Virus Vaccines Have Universal Immune Correlates of protection?. Issue 1 (January 2019) - Meyer, Michelle; Malherbe, Delphine C.; Bukreyev, Alexander
Abstract : Testing vaccine efficacy against the highly lethal Ebola virus (EBOV) in humans is almost impossible due to obvious ethical reasons and the sporadic nature of outbreaks. For such situations, the 'animal rule' was established, requiring the product be tested in animal models, expected to predict the response observed in humans. For vaccines, this testing aims to identify immune correlates of protection, such as antibody or cell-mediated responses. In the wake of the 2013–2016 EBOV epidemic, and despite advancement of promising candidates into clinical trials, protective correlates remain ambiguous. In the hope of identifying a reliable correlate by comparing preclinical and clinical trial data on immune responses to vaccination, we conclude that correlates are not universal for all EBOV vaccines. Highlights: Correlates of protection are crucial predictive tools for EBOV vaccine efficacy in humans. Different EBOV vaccines elicit distinct immune profiles defined by many parameters, including vaccine design and delivery. Immunological parameters identified in EBOV vaccine studies in animal models are not always reflected in clinical trials. Antibody and cell-mediated immune responses have different contributions to protection by different EBOV vaccines. Qualitative features of the antibody response, in addition to magnitude, can affect protection. Different vaccination routes can elicit qualitatively different immune responses. EBOV infection through different routes will likely require distinct vaccine-mediated protective mechanisms. There is currently no universal correlate of protection for EBOV vaccines, and it is unlikely that one will be identified in the near future.